Penguatan Literasi Numerasi Bagi Tenaga Pendidik Di SMP Negeri 3 Bangkala Kabupaten Jeneponto - Andi Mulawakkan Firdaus; Kasman; Sulfiati S; Andi Asminarti; Abd. Kadir Jaelani; Firkiawan Syah (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
This service aims to increase teachers' understanding of numeracy literacy and its application in learning. Numeracy literacy is an individual's ability to understand and use mathematical concepts, including symbols and numbers, to solve problems in everyday life. Based on the 2018 Program for International Student Assessment (PISA) report released by the Organization for Economic Co-operation and Development (OECD), the numeracy literacy level of students in Indonesia is still relatively low, ranking 74th out of 79 countries. Therefore, the role of teachers is very important in increasing students' numeracy literacy by integrating numeracy concepts into various subjects, not just mathematics. This service activity targeted 38 teachers at UPT SMP Negeri 3 Bangkala, Jeneponto Regency, who were given training and assistance in implementing numeracy-based learning strategies. The strategies used include contextual learning, problem-based learning, and active learning methods that involve students directly. It is hoped that this activity can increase teachers' understanding in teaching numeracy literacy effectively, thereby having an impact on increasing students' numeracy competence. The output of this activity includes increasing teacher understanding, implementing learning strategies that are more numeracy-based, as well as preparing learning modules as references in integrating numeracy literacy in various subjects. With this training, it is hoped that teachers will be able to develop numeracy learning that is more contextual and relevant, as well as contributing to improving the quality of mathematics learning in schools.